Remarkable enhancement in durability of ZrCo alloy against hydrogen induced disproportionation by Ti and Nb co-substitution. (5th March 2023) - Jat, Ram Avtar; Rawat, Deepak; Sharma, Abhishek; Parida, S.C.
Abstract: Considering the thermodynamic stability of various hydrides, a strategy has been employed to improve the hydrogen isotope storage properties of ZrCo alloy which involves partial co-substitution of Zr with Ti and Nb. Herein, alloys of composition Zr0.8 Ti0.2-x Nbx Co (x = 0.05, 0.1, 0.15) is prepared, characterized and the effect of Ti and Nb doping on hydrogen storage properties of parent ZrCo alloy is investigated. XRD analysis confirmed the formation of desired pure cubic phase of all the synthesized alloys similar to ZrCo phase. The presence of a single plateau in hydrogen desorption pressure-composition isotherms confirms single step hydrogen absorption-desorption behavior in Zr0.8 Ti0.2-x Nbx Co alloys. The equilibrium pressure of hydrogen desorption decreases marginally with increasing Nb content in Zr0.8 Ti0.2-x Nbx Co alloys which is further corroborated by differential scanning calorimetry measurements. Investigation of hydrogen induced disproportionation behavior in ITER-simulating condition revealed substantial impact of co-substitution of Ti and Nb on anti-disproportionation properties of ZrCo alloy. These remarkable properties make the Ti and Nb co-substituted quaternary alloys a desirable material for hydrogen isotope storage and delivery application. Graphical abstract: Image 1 Highlights: Prepared Zr0.8 Ti0.2-x Nbx Co alloys having single cubic phase. Hydrogen storage behavior of Zr0.8 Ti0.2-x Nbx Co alloys was investigated. Substitution of Zr with Ti and Nb significantly decreases the desorption temperature. Zr0.8 Ti0.05 Nb0.15 Co alloy has remarkably high anti-disproportionation properties.